The 2006 ESPN baseball encyclopedia - Palmer, Pete; Gillette, Gary; ESPN (Television network) (New York : Sterling, 2006)
Details statistics from United States baseball teams and players from 1900 through the previous season, including draft information, and provides lists of award winners and world champion teams.
Compilers: Gary Gillette and Pete Palmer.
Description based on: 4th edition, published 2007; title from title page.
Latest issue consulted: 2012.
Keywords: Baseball -- United States -- Statistics; Baseball -- Records -- United States